THE EFFECT OF CUSTOMER VALUE AND CUSTOMER EXPERIENCE ON REPURCHASE DECISIONS THROUGH CUSTOMER SATISFACTION ON GRAB ONLINE TRANSPORTATION (Survey of Grab Customers in Sleman Regency) - Nurahman, Ikhsan (FEB Universitas Sam Ratulangi Manado, 2021)
Abstract: The purpose of this study was to determine the direct influence of customer value and customer experience on repurchase decisions through customer satisfaction on online transportation Grab in Sleman. This type of research uses quantitative research with survey methods. The sample in this study is purposive sampling, namely the technique of determining the sample with certain considerations. Data collection in this study used a survey technique using a questionnaire. The results of the study include, customer value has a positive effect on repurchase decisions on Grab online transportation, customer experience has a positive effect on repurchase decisions on Grab online transportation, customer value has a positive effect on repurchase decisions through customer satisfaction on Grab online transportation, customer experience has an effect a positive impact on repurchase decisions through customer satisfaction on Grab online transportation.Â Abstrak: Tujuan dari penelitian ini adalah untuk mengetahui pengaruh langsung nilai pelanggan dan pengalaman pelanggan terhadap keputusan pembelian ulang melalui kepusasan pelanggan pada transportasi online Grab di Sleman. Jenis penelitian ini menggunakan penelitian kuantitatif dengan metode survei. Sampel dalam penelitian ini adalah purposive sampling yaitu teknik penentuan sampel dengan pertimbangan tertentu. Pengumpulan data pada penelitian ini menggunakan teknik survei menggunakan kuisioner. Hasil dari penelitian meliputi, nilai pelangganÂ berpengaruh positif terhadap keputusan pembelian ulang pada transportasi online Grab, pengalaman pelanggan berpengaruh positif terhadap keputusan pembelian ulang pada transportasi online Grab, nilai pelanggan berpengaruh positif terhadap keputusan pembelian ulang melalui kepuasan pelanggan pada transportasi online Grab, pengalaman pelanggan berpengaruh positif terhadap keputusan pembelian ulang melalui kepuasan pelanggan pada transportasi online Grab.